(untitled) (Itinera, 2023)
In this contribution, I discuss the status of comics particularly through the exemplification of Disney’s Dante parodies, in light of some ideas I take in from aestheticological reflection on improvisational art practices. In particular, L’Inferno di Topolino, the first of the great Italian Disney parodies, is paradigmatic for understanding the character of comics as a metafinational hybrid transmedium, capable of appropriating the contents of literary classics, bringing them to life in relation to the contemporary situation.